Islamic Education Management for Strengthening Early Childhood Character: A Multi-Site Qualitative Case Study in Indonesian Islamic Preschools - Munawaroh, Hidayatu; Wicaksono, A.Bagus; Hidayati, Salis Wahyu; Fatonah, Kuni; Sriyanto, Agus; Maulidia, Siti Nirmaya; Akmaliah, Untsa (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – This study examines how Islamic educational management embeds religious values in everyday character-building practices in Islamic preschools and identifies the organizational mechanisms that support or constrain their continuity. Design/methods/approach – A multi-site qualitative case study was conducted in three Islamic early childhood institutions in Wonosobo, Central Java, Indonesia. Data were collected from January to April 2026 through non-participant observations, semi-structured interviews with 21 participants (three principals, ten teachers, two administrative staff members, and six parents), and institutional document analysis. Data were analyzed through thematic coding, within-case analysis, cross-site comparison, and source triangulation.Findings – Management functions were present but integrated at different levels of operational maturity. Religious and character-building practices were implemented consistently, while planning remained broadly normative, staff coordination relied substantially on informal communication, and evaluation did not yet generate systematic feedback for program improvement. Character-building practices were most coherent when habituation, teacher role modeling, school culture, and home-school-community reinforcement supported one another.Research implications/limitations – The study is limited to three institutions in one regency and does not directly measure internal psychological change or long-term developmental outcomes. The findings therefore support analytical transfer rather than statistical generalization.Practical implications – Islamic preschool leaders should translate broad character goals into observable developmental indicators, institutionalize collaborative reflection, strengthen authentic assessment, and establish reciprocal family communication.Originality/value – The study proposes managerial value internalization as a contextually grounded explanation of how Islamic values are translated into organizational priorities, recurring practices, adult examples, shared expectations, and feedback processes that support their possible internalization by children.Paper type Research paper